Perón y el exceso: a los trabajadores los inventó Perón: Algunas pistas para comprender al kirchnerismo - Bruno, Lucas Ezequiel (Universidad Nacional de Villa María, 2018)
This article intends to interpret the relationship that was established between Perón and the workers from a strictly political perspective, arguing with the sociological interpretative frames. In this framework we will use certain notions of the political discourse theory of Ernesto Laclau (2013) and Chantal Mouffe (2011) and we will argue that Perón's intervention in the national political arena constituted politically and subjectively the labor movement - before the intervention of Perón could hardly be spoken of "workers movement" reason why we will argue in the later-. On the other hand, we are interested in staging the logic of the political constitution of peronism, that is to say, the form that politics acquired-logic that years later will be reproduced, in part, by Kirchnerism; here we will call it the logic of excess, as it expands and strengthens the expansion of community limits, as well as it overflows the imaginary of what is possible -from an impossibility-necessary-.